Validity and Reliability Test of the Learning Independence Questionnaire Instrument in Using Electronic Modules - Siti Imroatus Sa'adah; Jaslin Ikhsan (Postgraduate, University of Mataram, 2023)
This research aims to create an instrument that can measure students' learning independence by measuring the level of validity and reliability. The instrument is a questionnaire for student learning independence consisting of 41 statements (20 positive statements and 21 negative statements) with responses based on a Likert scale score of 1 to 5. The research location for the empirical test of learning independence was at SMAN 1 Kalasan class XII MIPA in 3 classes. The number of empirical trial participants was 99 students. The results of the empirical test of the learning independence questionnaire instrument were then analyzed using the Winstep Rasch model program. The quality of the instrument can be determined from the unidimensional assumption test, the suitability test of the statement items to the Rasch model (item fit), and the bias of the statement items with the help of the Winstep program. The results obtained were that in the validity calculation there was 1 invalid statement out of 41 existing statements, namely the statement